2013
DOI: 10.1186/1471-2334-13-12
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic primary tuberculous pleurisy with intense 18-fluorodeoxyglucose uptake mimicking malignant mesothelioma

Abstract: BackgroundThe pathogenesis of primary tuberculous pleurisy is a delayed-type hypersensitivity immunogenic reaction to a few mycobacterial antigens entering the pleural space rather than direct tissue destruction by mycobacterial proliferation. Although it has been shown that pulmonary tuberculosis induces 18-fluorodeoxyglucose (FDG) uptake in active lesions, little is known about the application of FDG positron emission/computed tomography (FDG PET/CT) to the management of primary tuberculous pleurisy.Case pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…When compared with the series by Goo et al [12] and Kim et al [13], SUV max values and %Delta SUV max in lung tuberculoma were found to be higher. 18 F-FDG SUV max values and %Delta SUV max values were not significantly different in benign and malignant lesions. These findings are in agreement with the data reported by Chen et al [15], who included a selected group of patients with an initial mean 18 F-FDG PET SUV of less than 2.5.…”
Section: Key Pointsmentioning
confidence: 68%
See 4 more Smart Citations
“…When compared with the series by Goo et al [12] and Kim et al [13], SUV max values and %Delta SUV max in lung tuberculoma were found to be higher. 18 F-FDG SUV max values and %Delta SUV max values were not significantly different in benign and malignant lesions. These findings are in agreement with the data reported by Chen et al [15], who included a selected group of patients with an initial mean 18 F-FDG PET SUV of less than 2.5.…”
Section: Key Pointsmentioning
confidence: 68%
“…In extrapulmonary TB, 18 F-FDG PET detects more tuberculous lesions than CT, is of value in assessing response to tuberculostatic treatment, and helps in diagnosing spinal infection and identifying TB-related spondylitis. 6.59) compared with inactive tuberculoma.…”
Section: Key Pointsmentioning
confidence: 99%
See 3 more Smart Citations